2015
DOI: 10.1093/hmg/ddu750
|View full text |Cite
|
Sign up to set email alerts
|

TBX1 protein interactions and microRNA-96-5p regulation controls cell proliferation during craniofacial and dental development: implications for 22q11.2 deletion syndrome

Abstract: T-box transcription factor TBX1 is the major candidate gene for 22q11.2 deletion syndrome (22q11.2DS, DiGeorge syndrome/Velo-cardio-facial syndrome), whose phenotypes include craniofacial malformations such as dental defects and cleft palate. In this study, Tbx1 was conditionally deleted or over-expressed in the oral and dental epithelium to establish its role in odontogenesis and craniofacial developmental. Tbx1 lineage tracing experiments demonstrated a specific region of Tbx1-positive cells in the labial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 75 publications
(94 reference statements)
2
38
0
Order By: Relevance
“…The TBX1 (Tbox transcription factor) gene is considered the major candidate for 22q11.2 deletion syndrome [Gao et al, 2015], being associated with cardiovascular defects [Lindsay et al, 2001;Jerome and Papaioannou, 2001], middle and inner ear defects, resulting in sensorineural hearing loss [Funke et al, 2001], and with craniofacial and dental Dantas et al Mol Syndromol 2015;6:242-247 DOI: 10.1159/000441243 246 development delay [Gao et al, 2015]; features we found in our patient.…”
Section: Discussionsupporting
confidence: 49%
“…The TBX1 (Tbox transcription factor) gene is considered the major candidate for 22q11.2 deletion syndrome [Gao et al, 2015], being associated with cardiovascular defects [Lindsay et al, 2001;Jerome and Papaioannou, 2001], middle and inner ear defects, resulting in sensorineural hearing loss [Funke et al, 2001], and with craniofacial and dental Dantas et al Mol Syndromol 2015;6:242-247 DOI: 10.1159/000441243 246 development delay [Gao et al, 2015]; features we found in our patient.…”
Section: Discussionsupporting
confidence: 49%
“…Low levels of PTH in Ns-HypoPT and end-organ resistance to PTH in PHP leads to hypocalcemia. Hypocalcemia is hypothesized as one of the potential causes of disturbances of the tooth development, e.g., enamel opacities and enamel hypoplasia (Garfunkel et al, 1979; Gao et al, 2015). Studies on dental manifestations of the various types of Ns-HypoPT and PHP, e.g., enamel hypoplasia, enamel opacities, hypodontia, root deviations, and eruption disturbances are, however, often mentioned with only few references (Goswami et al, 2009; Velez et al, 2009; Kamarthi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…TBX1 is a major candidate gene causal for 22q11 deletion syndrome associated with congenital heart defects resulting from incorrect left-to-right patterning important for asymmetric cardiac morphogenesis 42 as well as craniofacial and dental anomalies including cleft palate. 43 The LIM protein AJUBA has previously shown an association with soft tissue facial width phenotypes, 44,45 and it is also required for expression of early developmental genes that determine left-right body axis patterning. 46 As discussed above, SNAI3 was largely associated with skeletal phenotypes in malocclusion patients in our previous study.…”
Section: Discussionmentioning
confidence: 99%